Malaysian quality & satisfaction index for libraries (MyQSILib) - Noordin, Siti Arpah; Abdullah Sani, Mad Khir Johari; Sahid, Noor Zaidi; Masrek, Mohamad Noorman; Baharuddin, Mohammad Fazli (Universiti Teknologi MARA, Kedah, 2017)
Changes in consumer preferences as well as rapid advancement of ICT have huge impacts on library services and operations. In order to meet customer needs and demands as well as optimizing products and services, continuous assessment of customer satisfaction towards the provision of library and information product and services is very crucial. Assessing users’ satisfaction of library services as well as identifying their issues and problems are fundamental factors in order to meet the needs of library users. Studies and literature on library quality and satisfaction are widely being discussed by researchers, practitioners and academicians around the world, however, there is still very little literature on library quality and satisfaction framework being researched in Malaysia. Surveys are being carried out in Malaysian libraries to assess their users’ satisfaction, nevertheless, the instruments used to measure the quality and satisfaction of their services varies and inconsistent. As a result, it is difficult to benchmark the performance of a library with its competitors of the same domain (Academic, Special, Public or School Libraries) which indirectly may not advocate the competitiveness drives among Malaysian libraries. Thus, it is an opportunity for the MyQSILib project to develop an intellectual framework in the area of library measurement and evaluation for Malaysian libraries. It seeks to develop a rigorous library performance measurement framework and instrument that fit the Malaysian context and setting. Conversely, MyQSILib project intent to develop the theoretical and methodological knowledge necessary for the measurement and evaluation of library and information services in Malaysia. The objectives of the MyQSILib project include:  to identify conceptual requirements for assessing Malaysian library and information services  to develop a standard performance measurement framework and instrument of assessing Malaysian library services quality and customer satisfaction The project will engage various methodologies of measurement and evaluation in Malaysian library services. A library assessment of quality and satisfaction software package (MyQSILib) will be developed as an outcome of the project. It will serve as a benchmark tool for library productivity. The contributions of the research project pertaining to the Malaysia Quality & Satisfaction Index for Libraries include:  Empirical context: Empirical exploration in understanding the conceptual requirements for assessing Malaysian library and information services Quality & Satisfaction will generate a framework which can be used as a strategic means for benchmarking library productivity. The instrument for measuring the Quality and Satisfaction Index may become a national measurement tool for library as it gives a unique insight of library services in Malaysia. Therefore, the framework and instrument may be used to facilitate a solid foundation for all types of libraries in assessing and benchmarking their service quality and customer satisfaction • Theoretical/conceptual context: This research study could fill some knowledge gaps on the library measurement and evaluation. It provides a broader understanding of the phenomenon based on the contextual scenarios within the Malaysian library setting. Furthermore, studies relating to developing a standard Quality & Satisfaction Index for Malaysian libraries have not, to date, been undertaken, therefore, besides contributing to the empirical evidence, theoretically and conceptually, discussions on Malaysian library measurement and evaluation will add on to the body of knowledge either to be adopted as a baseline or even to be reviewed in the future research. • Methodological context: The research framework and the adoption of the mixed method approach may be used in other research either totally or partially. Since the virtual and digital technology is now becoming significant tools in today’s activities, the technology need to be capitalized. Discussions and experience in using this method could give new insights of this alternative data collection technique